(untitled) (The Pakistan Development Review, 1987)
During the last few decades there has been a sharp transition in economic doctrine, within the context of economic growth, on the relative contributions of agriculture and industrial development. There has been a shift away from the earlier ’industrial fundamentalism’ to an emphasis on the significance of growth in agricultural productivity and production. The focus, especially in the context of the present-day less developed countries like Pakistan, has sharpened with the rapid growth in demand for food, resulting from the increasing growth in population and the high income-elasticities of the demand for food. Coupled with this is the transition from resource-based agriculture to science-based agriculture. Agricultural economists are unanimous in the view that by the end of this century all increases in world food production will come from higher yields, i.e. increased output per hectare. This increasing emphasis on ’land-saving’ technology to increase productivity and production has resuited from the growing population pressures on land and declining land-man ratios. Agricultural research has come to the fore in providing technologies that increase productivity and production. However, these technologies do not explicitly take into account the equity aspects of the problem. The extent to which the poor gain or lose from the introduction of a new agricultural technology depends on a host of complex and interrelated socio-economic and political factors such as the existing distribution of productive resources, access to modem inputs, the structure of the market, etc.